(untitled) (Journal of Scientific Research, 2024)
When utilising traditional machining processes, convincing and competent processing with ultra precision of superalloys are highly difficult and stiff task. Accordingly, the authors recognised a need for non-conventional machining (NCM) for processing of alloy 718 (other name ‘Inconel 718’ or UNS N07718) using wire electric discharge machining (WEDM). L16 Taguchi’s orthogonal array has been utilised for preferred design of experiment. Pulse on duration (Ton), pulse off duration (Toff), wire speed (Uw), and current (I) has been selected as control factors to study the effects of performance. Material removal rate (MRR), Kerf Width (KW) and Surface Roughness (SR) has been assessed as an output performance. Analysis of variance (ANOVA) is also performed and found that I has the greatest influence on MRR while Uw is lowest, with contribution of 47.11 % and 6.05 % respectively. For KW, Toff is greatest influential factor while I is lowest, with contribution of 35.39 % and 4.35 %. For SR, Ton is greatest influential factor while Toff is lowest, with contribution 87.8 % and 3.27 %. Also error between the actual and predicted values is below 5 %. For MRR, the error is 4.20 % while for KW and SR, it is 0.31 % and 2.21 % indicating close alignment with the achieved value.